Interconnection between Business and Activism in Managing Waste: Case in Community-Based Waste Organization in Small Island Tourism of Gili Trawangan, Indonesia - Anugrah, Galang (Journal of Indonesian Tourism and Development Studies, 2022)
Much has been studied about community-based waste organizations in Indonesia. Yet, most studies are concentrated in urban areas, and only some studies try to build a historical and comprehensive analysis of how the practice could exist, especially in a small island tourism context. To extend the discussion within this field, this study aims to analyze the trajectory and characteristics of community-based waste management in the Gili Trawangan since this organization has a unique character: It is a fusion between a waste transportation business, a waste bank, and a waste clean-up program. By using qualitative methods, case study approaches, and interviewing 13 key informants, this study concludes as follows. The Community Concern for the Environment (FMPL), the only community-based organization in Gili Trawangan’s waste management sector, emerged and existed on a specific historical trajectory with the development of the tourism industry. The formation of this organization is inseparable from the group of local people in business’s influence, yet along the way, the contribution of environmental NGOs on this island plays a significant role in promoting activism and environmental-based management. Hence, the interconnection between business (economy) interests and activism (environment) characterizes the uniqueness of how this island manages its waste. Keywords: Community-Based Waste Management, Gili Trawangan, Indonesia, Small Island Tourism.